Biopolymers used as drying aids in spray- drying and freeze-drying of fruit juices and pulps - Telis, Vânia Regina Nicoletti [UNESP]; Martínez-Navarrete, Nuria (Taylor & Francis, 2012)
Powdered fruit juices and pulps might constitute good alternatives to convenient and healthy food products or ingredients to formulated foods. Nevertheless, due to the high content of low-molar-mass constituents in their composition, these products are susceptible to a series of technical problems during drying and storage.